THE PSYCHOLOGICAL IMPACT OF COLORS IN DIFFERENT LANGUAGES AND CULTURES (Ustozlar uchun, 2026)
Color is a universal phenomenon, yet its meanings and psychological influences vary significantly across different languages and cultures. While some colors evoke similar emotional reactions globally, many associations are shaped by cultural history, religion, social norms, and linguistic categorization. This article examines how colors influence human psychology and how these effects differ across cultures, drawing on examples from Western, Eastern, and Central Asian traditions. It also discusses how linguistic and cultural contexts shape emotional responses to color and influence communication, symbolism, and perception.